Self‐Oriented Nanojoining of Silver Nanowires via Surface Selective Activation. (8th March 2013) - Peng, Peng; Liu, Lei; Gerlich, Adrian P.; Hu, Anming; Zhou, Y. Norman
<x xml:space="preserve">Abstract</x> Silver nanowires are joined and form monocrystalline V‐shaped or zig‐zag silver prisms. Selective activation of surfaces and self‐orientation of lattices promote the joining of silver nanowires under cold conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>